2015
DOI: 10.1038/ng.3293
|View full text |Cite
|
Sign up to set email alerts
|

A Sleeping Beauty forward genetic screen identifies new genes and pathways driving osteosarcoma development and metastasis

Abstract: Osteosarcomas are sarcomas of the bone, derived from osteoblasts or their precursors, with a high propensity to metastasize. Osteosarcoma is associated with massive genomic instability, making it problematic to identify driver genes using human tumors or prototypical mouse models, many of which involve loss of Trp53 function. To identify the genes driving osteosarcoma development and metastasis, we performed a Sleeping Beauty (SB) transposon-based forward genetic screen in mice with and without somatic loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
245
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(260 citation statements)
references
References 84 publications
8
245
2
1
Order By: Relevance
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, in many cases, only a single transposon insertion was present at a CCG in tumor cells, suggesting that many CCGs are functioning as haploinsufficient TSGs. This is similar to what has been observed in other SB mutagenesis screens performed in solid tumors (18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Csupporting
confidence: 77%
“…Identification of Trunk Driver Genes. Most CCGs identified by SB mutagenesis are thought to function during late stages of tumor progression (18)(19)(20)(21)(22)(23)(24)(25)(26). To identify the CCGs that function early in mammary tumor development, we selected transposon insertion sites represented by the highest number of sequencing reads (SB insertions in the CCG in ≥3 tumors with ≥9 reads per tumor), arguing that these insertions would be present in the largest number of tumor cells.…”
Section: Sb Mutagenesis Promotes the Development Of Multiple Breast Cmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often associated with massive chromosomal rearrangements, cytogenetic aberrations, and numerous mutations [25]. Numerous cytogenetic and molecu-lar studies of osteosarcoma have been conducted in recent years yielding interesting results but often with conlicting indings [26].…”
Section: Chromosomal Abnormalitiesmentioning
confidence: 99%
“…It was reported that Sema6D regulates the late-phase activity of T cells during the primary immune response (14), and it functions as a promoter of tissue remodeling (15) and tumorigenesis (16). Additionally, Sema6D also functions as a ligand for plexin-A1 during T cell-dendritic cell interactions (6).…”
Section: Introductionmentioning
confidence: 99%